PEMBELAJARAN AKSARA PEGON PADA INSTANSI PENDIDIKAN FORMAL (STUDI FENOMENOLOGI DI MI NU KH. MUKMIN SIDOARJO) - Kuswanto, Aris; Adhimah, Iftirohatul; Aziz, Ahmad Musonnifin (Jurnal Muassis Pendidikan Dasar, 2025)
Pegon script is one of the valuable legacies of the scholars who spread Islam in the archipelago, especially for Nahdlatul Ulama'. However, its existence has decreased until now except in the Salaf Islamic Boarding Schools. On the other hand, MI NU KH. Mukmin as a formal educational institution tries to help preserve Pegon script in schools. This study aims to describe the background, objectives, and elements of Pegon script learning, as well as its influence on formal educational institutions, especially MI NU KH. Mukmin. This study uses a phenomenological approach. Data collection techniques use in-depth interviews and literature studies. The results of the study show that Pegon script learning is one of the compulsory subjects at MI NU KH. Mukmin in a local content. There is also a Pegon script learning guidebook, learning evaluation, and supporting learning media like other subjects. In addition, after students have completed learning the Pegon script, learning continues with learning the Safinatun Najah book until grade 6. On the other hand, learning the Pegon script is to equip students, because most of the graduates of MI NU KH. Mukmin Sidoarjo continue their education to Islamic boarding schools. MI NU KH. Mukmin also received appreciation for the 1st Place PWNU East Java Award in 2023 through its superior programs, one of which is learning the Pegon script.